Implementation of Relationship Marketing Strategy at Lyco Coffee Temanggung, Central Java: Implications for Repeat Purchases - Dahlan Iswandar (Journal of Organizational Performance and Analysis, 2025)
The purpose of this study was to analyze the effect of service quality on repurchase decisions, a case study of Lyco Coffee and Place consumers in Temanggung, Central Java. The number of samples in this study was 75 respondents using the incidental sampling method. This study used multiple linear regression analysis methods. The results of this study indicate that there is a simultaneous influence of variables (promotion and service quality) on repurchase decisions, which can be seen from the significance value below 0.05 and the calculated F value of (63.522) ˃ F table (3.12). The results of this study also show that the calculated t value for the promotion variable is 3.557, service quality is (4.302) greater than the t table (1.993), so it is stated that there is an influence on repurchase decisions. In the determination test, there is an influence of 62.8% of the independent variables (promotion and service quality) on the dependent variable (repurchase decisions). Meanwhile, 37.2% is influenced by other variables and is not included in this regression analysis, such as location, price, brand image, brand equity, and others.